Optimizing the Role of Family as Main Support for Elderly Through Social Counseling - Rizqi Alamsyah; Muhamad Khasbi Hanif; Habieb Abdillah Ali Affaf; Ulin Nihayah (Faculty Ushuluddin, Adab and Dakwah UIN Palangka Raya, 2025)
Indonesia is undergoing a rapid demographic transition toward an aged society, shifting the long-term caregiving burden heavily onto the informal family structure. Within the local sociocultural context of filial piety, the family is the primary pillar of eldercare. However, modern socioeconomic pressures have eroded domestic capacities, trapping productive-age individuals within a highly stressful dual-obligation matrix known as the